Educational leadership or administration during a busy workday: The status and roles of assistant principals - Sigurðardóttir, Dóra Margrét; Ragnarsdóttir, Guðrún (Menntavísindasvið Háskóla Íslands, 2020)
Research has shown that assistant principals have growing roles in administration and educational leadership as school complexity and demands for student achievement increase (Börkur Hansen, Ólafur H. Jóhannsson, & Steinunn Helga Lárusdóttir, 2002; Grodzki, 2011). Many scholars highlight how assistant principals hold multifaceted roles, facing many challenges on the job. Furthermore, assistant principals generally experience their roles as being unclear and poorly defined (Oleszewski, Soho, & Barnett, 2011; Petrides, Jimes, & Karaglani, 2014).The terms administration and leadership are often used to describe the roles of school leaders. Whereas administration refers to tasks related to finances, human resources and daily management of the school (Gardner, 2000; Sergiovanni, 2009), leadership has more to do with leading the teachers in their roles as educators (Hoy & Miskel, 2012).The role of assistant principal is relatively new in the Icelandic school system. It seems to be rather poorly defined, and it is unclear what it entails regarding the law and regulations where assistant principals are generally not mentioned (lög um grunnskóla nr. 91/2008 (Compulsory School Act); mennta- og menningarmálaráðuneytið, 2013 (Ministry of Education Science and Culture)).The aim of this article is to shed light on how assistant principals in compulsory schools in Reykjavík experience their roles and status within the schools and their view of educational leadership and administration as focus areas. The study is based on in-depth semi structured interviews with eight assistant principals in the City of Reykjavík, who were randomly selected. Data was analyzed using interpretive phenomenology (Braun & Clarke, 2013; Smith & Osborn, 2008).In order to investigate how assistant principals experience their roles and status we asked the following:What are the assistant principals’ roles within the compulsory schools in Reykjavík and what are their main tasks?What views do assistant principals have for their ...